The Chancellor’s Leadership Style in Improver Lecturer Performance at the University of Muhammadiyah Jember: Gaya Kepemimpinan Rektor Dalam Meningkatkan Kinerja Dosen Di Universitas Muhammadiyah Jember - wakit , Saipul; Nurdiana, Ilfi; Yuliana, Indah (Universitas Muhammadiyah Sidoarjo, 2021)
In the context of higher education, leadership is a very strategic element, because leadership has a role to encourage change in an organization. Leadership in higher education organizations, of course, the Chancellor is a real leader who plays a role in determining the performance of higher education organizations. The Chancellor as the highest leader in higher education institutions is one element that plays an important role in moving the performance of existing human resources. Besides that, one of the factors that becomes a benchmark for the success of a university is the performance of lecturers. With regard to these assumptions, it can be formulated that the purpose of this research has a concrete goal, namely to analyze and describe how the leadership style of the Chancellor of UM Jember in motivating, trying, and evaluating lecturer performance. The research method uses a qualitative approach with a case study design at UM Jember with data collection techniques through interviews, observation and documentation